A Fast, Multi-Period Economic Load Dispatch for Large-Scale Power Systems - Ab Ghani, Mohd Ruddin (2002)
This paper presents optimizes economic load dispatch for large-scale power systems. The purpose is to achieve the required minimization of the operational cost of power generation. Linear Programming, Lagrangian Relaxation and Network Flow Programming methods were used. The combined algorithm used appear to be fast enough to meet the computation resource requirement of the system and to minimize the operating cost of generation units. An economic load dispatch with six period intervals has been formulated and successfully computed. The results found from the algorithm appears to be modest in both optimizing the operational cost and achieving fast computation time.